USING QUALITATIVE RESEARCH IN IDENTIFYING AND DEVELOPING YOUNG TALENTS IN ELITE AMATEUR GOLF IN MALAYSIA - Zainudin Omar; Mohd Rom Muslim; Md Zawawi Abu Bakar (Jurnal Penyelidikan Sains Sosial, 2021)
Qualitative methodology is now used more frequently in sports management research especially in understanding athletes’ motivation, beliefs and perceptions. This study aims to provide an overview of applying qualitative methodology to identify, select and develop young talents in elite amateur golf to meet the demands of national and international competitions. By talking directly with participants who are industry experts can give a good understanding of the process of producing top amateur golfers. The participants comprised of seven professional coaches and one official of the national golf body who were selected through a purposive sampling technique. Thus, the researcher is the key instrument in gathering information through semi-structured and open-ended interviewing, to get the range of information such as their views on perspectives and meanings that the participants hold in the area of study. In conclusion, the researcher emphasizes that the qualitative method was suitable to get the data regarding golf development.